Cascade hole positive electrode and preparation method thereof
By designing the ladder pore positive electrode on the thick electrode sheet of the lithium-ion battery, the structure of high porosity of the outer layer and low porosity of the inner layer is solved, and the battery's magnification, circulation and safety performance are significantly improved.
Patent Information
- Application Number
- CN202411900004.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The difficulty of infiltration of the thick electrode sheet electrolyte increases and the lengthening of the lithium ion transmission path, resulting in poor magnification and circulation performance of the lithium ion battery and prone to thermal runaway.
The design of a cascade pore positive electrode is adopted, and the cascade pore positive electrode with low porosity and high porosity of the inner layer on the surface of the aluminum foil is constructed to improve the electrolyte wetting ability and lithium ion transmission path.
It achieves excellent rate and cycle performance, with a charge and discharge cycle life of more than 1,000 cycles at 5C, and at the same time, it reduces the hazards of the battery when thermal runaway and improves the safety performance of the battery.
Smart Images

Figure CN119725405A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a negative electrode of a lithium ion battery. Background Art
[0002] Lithium-ion batteries have been widely used in portable electronic products, electric vehicles, energy storage systems and other fields. With the development of society, the lithium-ion battery market has expanded, especially the rapid growth in electric vehicle sales in recent years. People have put forward higher requirements for standby time or driving range. How to further improve the energy density of lithium batteries has become a key issue that the industry needs to solve urgently. Thick electrode design can increase the active material load of the electrode and reduce the proportion of inactive materials in the single cell. It is one of the effective means to improve the energy density of the battery. However, as the thickness of the electrode increases, the difficulty of electrolyte infiltration increases, the lithium ion transmission path becomes longer, and the battery impedance increases, which leads to poor battery rate and cycle performance.
[0003] In order to overcome the above problems, the method of increasing porosity can be used to improve wettability during the preparation of thick positive electrodes, increase the contact between active materials and electrolytes, and thus shorten the lithium ion transmission path. Patent CN102324493A adopts a double-coating structure, and adjusts the content of the inner and outer conductive agents, the rolling pressure, and the addition of pore-forming agents to prepare an inner layer with high conductivity and low porosity, and an outer layer with low conductivity and high porosity, so as to improve the electrochemical performance of thick electrodes. However, the two rolling processes increase the manufacturing process and increase the production cost. Patent CN114400301A constructs a channel array by performing ion beam etching, reactive ion etching, inductively coupled plasma etching, focused electron beam etching, focused ion beam and other methods on thick electrodes, and constructs a tree-like electrolyte channel by adding lithium salt additives dissolved in the electrolyte in the thick electrode. There are still problems such as complex processes and the properties of lithium salt additives are easily changed during baking, transfer and other production processes. Patent CN115275094A uses a thin needle row to puncture micropores in the thick electrode pole piece, forming a micropore array on the surface of the pole piece coating material, thereby improving the fast charging performance of the battery. However, during the puncture process, the electrode material at the needle tip position will inevitably be squeezed to the surrounding area, resulting in uneven pole piece surface and increased thickness, which affects battery performance. Therefore, it is necessary to design a thick pole piece and its preparation method that can ensure sufficient electrolyte infiltration of the thick pole piece, shorten the lithium ion transmission path, and have a simple process.
[0004] In addition, during the use of lithium-ion batteries, thermal runaway may occur due to factors such as internal short circuits, overcharging, over-discharging, and high temperature environments. In order to reduce thermal runaway of lithium-ion batteries, additional flame retardants are usually required. For example, patent publication number CN112913056A discloses an electrode with a flame retardant additive, a preparation method and system for an electrode with a flame retardant additive, and the use of an electrode with a flame retardant additive. The electrode active material includes a lithiated compound core and flame retardant embedded particles partially retained on the surface of the lithiated compound core. The patent directly uses particles such as zinc borate, magnesium hydroxide, magnesium oxide, magnesium carbonate, magnesium bicarbonate, aluminum hydroxide, aluminum oxide, aluminum hydroxide oxide, antimony oxide, ammonium sulfate, ammonium carbonate, urea and polyacrylonitrile as flame retardants, and the uniformity of dispersion is subject to certain limitations. Summary of the invention
[0005] In order to solve the technical problems of increased difficulty in electrolyte infiltration of thick electrodes, longer lithium ion transmission path, poor battery rate and cycle performance, and easy thermal runaway, the present invention proposes a cascade pore positive electrode and a preparation method thereof. By introducing a pore-forming agent into the outer layer, a cascade pore positive electrode with low inner porosity and high outer porosity composited on the surface of aluminum foil is constructed. The high porosity of the outer layer solves the problems of poor electrolyte wettability and long lithium ion transmission path caused by thick electrodes. Thanks to these advantages, the cascade pore positive electrode has good rate and cycle performance, and the preparation method is simple and does not produce toxic substances. The residual substance after the pore-forming agent is heated and decomposed is magnesium oxide, which can be used as a flame retardant to reduce the harmfulness of lithium-ion batteries during thermal runaway and improve battery safety performance.
[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] A graded-pore positive electrode comprises a current collector, on which a first porous active material layer and a second porous active material layer are sequentially arranged; the thickness of the first porous active material layer is 20-200 μm, and the thickness of the second porous active material layer is 50-320 μm.
[0008] A method for preparing a hierarchical pore positive electrode comprises the following steps:
[0009] (1) mixing a positive electrode active material I, a conductive agent I, an adhesive I and a solvent I into a first slurry, and coating the first slurry on a current collector, and removing the solvent I to form a first porous active material layer;
[0010] (2) mixing the positive electrode active material II, the conductive agent II, the adhesive II, the pore former and the solvent II into a second slurry, and coating the second slurry on the first porous active material layer, and removing the solvent II to form a second porous active material layer;
[0011] (3) heat-treating the current collector obtained in step (2) to remove the pore-forming agent in the second porous active material layer, thereby obtaining a graded pore positive electrode.
[0012] The positive electrode active material I and the positive electrode active material II are independently selected from LiFePO4, LiMn2O4 and LiNi x Co y Mn 1-x-y Any one of O2(0≤x≤1, 0≤y≤1).
[0013] The conductive agent I and the conductive agent II are independently selected from any one of carbon black, carbon nanotubes, carbon fibers and Ketjen black.
[0014] The adhesive I and the adhesive II are independently selected from any one of polyvinylidene fluoride, polytetrafluoroethylene and polyimide.
[0015] The solvent I and the solvent II are independently selected from any one of water, ethanol, N-methylpyrrolidone, N,N-dimethylacetamide, dimethylformamide and toluene.
[0016] The pore-forming agent is nitrite.
[0017] The nitrite is magnesium nitrite.
[0018] In the step (1), the mass ratio of the positive electrode active material I, the conductive agent I and the adhesive I is (6-9.8): (0.1-2): (0.1-2).
[0019] In the step (2), the mass ratio of the positive electrode active material II, the conductive agent II, the adhesive II and the pore-forming agent is (4-9): 0.1-2: 0.1-2: (0.5-6).
[0020] The heat treatment temperature is 100-200° C. and the time is 6 h to 24 h.
[0021] Beneficial effects of the present invention:
[0022] 1. The present invention constructs a hierarchical pore positive electrode with low inner porosity and high outer porosity composited on the surface of aluminum foil by introducing a pore-forming agent into the outer layer. The high porosity of the outer layer solves the problems of poor electrolyte wettability and long lithium ion transmission path caused by thick electrodes. Thanks to these advantages, the hierarchical pore positive electrode has excellent rate and cycle performance. The cycle life exceeds 1000 cycles of charge and discharge cycles at a 5C rate.
[0023] 2. The preparation method of the present invention is simple and easy to implement.
[0024] 3. The preparation method described in this specification is simple. The residual substance after the pore-forming agent is heated and decomposed is magnesium oxide, which can be used as a flame retardant to reduce the hazard of lithium-ion batteries during thermal runaway and improve battery safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 A schematic diagram of a graded pore positive electrode provided by the present invention.
[0027] Figure 2 This is a scanning electron microscope (SEM) image of the hierarchical pore positive electrode prepared in Example 1 of the present invention, including a cross-sectional view and a top view. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] A hierarchical pore positive electrode, the structure of which is as follows Figure 1 As shown, it includes a current collector, on which a first porous active material layer and a second porous active material layer are sequentially arranged; the preparation method includes the following steps:
[0031] (1) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride is 8:1:1, dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on a 12μm aluminum foil to form the first porous active material layer.
[0032] (2) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the pore-forming agent is magnesium nitrite, and the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride: magnesium nitrite is 8:1:1:3. Dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on the first porous active material layer to form the second porous active material layer.
[0033] (3) The electrode obtained in step (2) is dried at 60°C and then roll-pressed. The electrode obtained after rolling is vacuum-heated at 150°C for 8 hours to obtain a graded pore positive electrode, wherein the first porous active material layer is 90 μm and the second porous active material layer is 90 μm. Figure 2 Scanning electron microscope (SEM) images of the hierarchical hole positive electrode, including cross-sectional and top views.
[0034] (4) The rolled hierarchical pore positive electrode is assembled into a lithium metal battery, the negative electrode is a metal lithium foil, and the electrolyte solute is 1 mol·L -1 The LiPF6 was prepared by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and 5%wt of fluoroethylene carbonate (FEC) was added.
[0035] (5) The prepared lithium metal battery was charged and discharged between 2.2 and 3.9 V (1C current density of 150 mA g -1 ), and the electrochemical properties are shown in Table 1.
[0036] Example 2
[0037] A hierarchical pore positive electrode, the preparation method comprises the following steps:
[0038] (1) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride is 8:1:1, dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on a 12μm aluminum foil to form the first porous active material layer.
[0039] (2) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the pore-forming agent is magnesium nitrite, and the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride: magnesium nitrite is 8:1:1:6. Dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on the first porous active material layer to form the second porous active material layer.
[0040] (3) The electrode obtained in step (2) is dried at 60°C and then roll-pressed. The electrode obtained after rolling is vacuum-heated at 150°C for 8 hours to obtain a graded pore positive electrode, wherein the first porous active material layer is 90 μm and the second porous active material layer is 90 μm.
[0041] (4) The rolled hierarchical pore positive electrode is assembled into a lithium metal battery, the negative electrode is a metal lithium foil, and the electrolyte solute is 1 mol·L -1The LiPF6 was prepared by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and 5%wt of fluoroethylene carbonate (FEC) was added.
[0042] (5) The prepared lithium metal battery was charged and discharged between 2.2 and 3.9 V (1C current density of 150 mA g -1 ), and the electrochemical properties are shown in Table 1.
[0043] Example 3
[0044] A hierarchical pore positive electrode, the preparation method comprises the following steps:
[0045] (1) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride is 8:1:1, dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on a 12μm aluminum foil to form the first porous active material layer.
[0046] (2) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the pore-forming agent is magnesium nitrite, and the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride: magnesium nitrite is 8:1:1:0.5. Dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on the first porous active material layer to form the second porous active material layer.
[0047] (3) The electrode obtained in step (2) is dried at 60°C and then roll-pressed. The electrode obtained after rolling is vacuum-heated at 150°C for 8 hours to obtain a graded pore positive electrode, wherein the first porous active material layer is 90 μm and the second porous active material layer is 90 μm.
[0048] (4) The rolled hierarchical pore positive electrode is assembled into a lithium metal battery, the negative electrode is a metal lithium foil, and the electrolyte solute is 1 mol·L -1 The LiPF6 was prepared by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and 5%wt of fluoroethylene carbonate (FEC) was added.
[0049] (5) The prepared lithium metal battery was charged and discharged between 2.2 and 3.9 V (1C current density of 150 mA g -1 ), and the electrochemical properties are shown in Table 1.
[0050] Example 4
[0051] A hierarchical pore positive electrode, the preparation method comprises the following steps:
[0052] (1) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride is 8:1:1, dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on a 12μm aluminum foil to form the first porous active material layer.
[0053] (2) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the pore-forming agent is magnesium nitrite, and the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride: magnesium nitrite is 8:1:1:0.5. Dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on the first porous active material layer to form the second porous active material layer.
[0054] (3) The electrode obtained in step (2) is dried at 60°C and then roll-pressed. The electrode obtained after rolling is vacuum-heated at 90°C for 8 hours to obtain a graded pore positive electrode, wherein the first porous active material layer is 90 μm and the second porous active material layer is 90 μm.
[0055] (4) The rolled hierarchical pore positive electrode is assembled into a lithium metal battery, the negative electrode is a metal lithium foil, and the electrolyte solute is 1 mol·L -1 The LiPF6 was prepared by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and 5%wt of fluoroethylene carbonate (FEC) was added.
[0056] (5) The prepared lithium metal battery was charged and discharged between 2.2 and 3.9 V (1C current density of 150 mA g -1 ), and the electrochemical properties are shown in Table 1.
[0057] Comparative Example 1
[0058] A method for preparing a double-layer positive electrode without hierarchical pores comprises the following steps:
[0059] (1) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride is 8:1:1, dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on a 12μm aluminum foil to form the first porous active material layer.
[0060] (2) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride is 8:1:1, dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on the first porous active material layer to form the second porous active material layer.
[0061] (3) The electrode obtained in step (2) is dried at 60°C and then roll-pressed. The electrode obtained after rolling is vacuum heated at 150°C for 8 hours to obtain a double-layer positive electrode without hierarchical pores, wherein the first porous active material layer is 90 μm and the second porous active material layer is 90 μm.
[0062] (4) The rolled hierarchical pore positive electrode is assembled into a lithium metal battery, the negative electrode is a metal lithium foil, and the electrolyte solute is 1 mol·L -1 The LiPF6 was prepared by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and 5%wt of fluoroethylene carbonate (FEC) was added.
[0063] (5) The prepared lithium metal battery was charged and discharged between 2.2 and 3.9 V (1C current density of 150 mA g -1 ), and the electrochemical properties are shown in Table 1.
[0064] Comparative Example 2
[0065] A method for preparing a hierarchical pore positive electrode:
[0066] (1) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the pore-forming agent is magnesium nitrite, the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride: magnesium nitrite is 8:1:1:2, dry-grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on a 12 μm aluminum foil to form the first porous active material layer.
[0067] (2) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride is 8:1:1, dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on the first porous active material layer to form the second porous active material layer.
[0068] (3) The electrode obtained in step (2) is dried at 60°C and then roll-pressed. The electrode obtained after rolling is vacuum-heated at 150°C for 8 hours to obtain a graded pore positive electrode, wherein the first porous active material layer is 90 μm and the second porous active material layer is 90 μm.
[0069] (4) The rolled hierarchical pore positive electrode is assembled into a lithium metal battery, the negative electrode is a metal lithium foil, and the electrolyte solute is 1 mol·L -1 The LiPF6 was prepared by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and 5%wt of fluoroethylene carbonate (FEC) was added.
[0070] (5) The prepared lithium metal battery was charged and discharged between 2.2 and 3.9 V (1C current density of 150 mA g -1 ), and the electrochemical properties are shown in Table 1.
[0071] Table 1 Electrochemical performance
[0072]
[0073] As shown in Table 1, compared with Comparative Example 1, the positive electrode with stepped pores in Example 1 has better discharge capacity and cycle stability than the positive electrode without stepped pores. The cycle life exceeds 1000 cycles of charge and discharge cycles at a rate of 5C. Compared with Comparative Example 2, the positive electrode with stepped pores in Example 1 with low inner porosity and high outer porosity has better electrolyte wettability and a short lithium ion transmission path than the positive electrode with stepped pores with high inner porosity and low outer porosity. Better electrochemical performance is obtained.
[0074] Example 5
[0075] A hierarchical pore positive electrode, the preparation method comprises the following steps:
[0076] (1) The positive electrode active material is lithium manganese oxide LiMn2O4, the conductive agent is Ketjen black, the binder is polyvinylidene fluoride, the mass ratio of lithium manganese oxide: Ketjen black: polyvinylidene fluoride is 6:0.1:2, dry grind and mix evenly, then add 1.5 times the mass of solvent N,N-dimethylacetamide to the mixture, stir and mix evenly, and coat it on a 12μm aluminum foil to form the first porous active material layer.
[0077] (2) The positive electrode active material is lithium manganese oxide LiMn2O4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the pore-forming agent is magnesium nitrite, the mass ratio of lithium manganese oxide: carbon black: polyvinylidene fluoride: magnesium nitrite is 9:2:0.1:3, dry-grind and mix evenly, then add twice the mass of solvent N,N-dimethylacetamide to the mixture, stir and mix evenly, and coat it on the first porous active material layer to form the second porous active material layer.
[0078] (3) The electrode obtained in step (2) is dried at 60°C and then roll-pressed. The electrode obtained after rolling is vacuum heated at 100°C for 24 hours to obtain a hierarchical pore positive electrode, wherein the first porous active material layer is 20 μm and the second porous active material layer is 320 μm.
[0079] (4) The rolled hierarchical pore positive electrode is assembled into a lithium metal battery, the negative electrode is a metal lithium foil, and the electrolyte solute is 1 mol·L -1 The LiPF6 was prepared by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and 5%wt of fluoroethylene carbonate (FEC) was added.
[0080] (5) The prepared lithium metal battery was charged and discharged between 3.0 and 4.2 V (1C current density was 120 mA g -1 ).
[0081] Example 6
[0082] A hierarchical pore positive electrode, the preparation method comprises the following steps:
[0083] (1) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polytetrafluoroethylene, the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride is 9.8:2:0.1, dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on a 12μm aluminum foil to form the first porous active material layer.
[0084] (2) The positive electrode active material is lithium iron phosphate LiFePO4, the conductive agent is carbon black, the binder is polyvinylidene fluoride, the pore-forming agent is magnesium nitrite, and the mass ratio of lithium iron phosphate: carbon black: polyvinylidene fluoride: magnesium nitrite is 4:0.1:2:6. Dry grind and mix evenly, then add twice the mass of solvent NMP to the mixture, stir and mix evenly, and coat it on the first porous active material layer to form the second porous active material layer.
[0085] (3) The electrode obtained in step (2) is dried at 60°C and then roll-pressed. The electrode obtained after rolling is vacuum heated at 200°C for 6 hours to obtain a graded pore positive electrode, wherein the first porous active material layer is 200 μm and the second porous active material layer is 50 μm.
[0086] (4) The rolled hierarchical pore positive electrode is assembled into a lithium metal battery, the negative electrode is a metal lithium foil, and the electrolyte solute is 1 mol·L -1 The LiPF6 was prepared by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and 5%wt of fluoroethylene carbonate (FEC) was added.
[0087] (5) The prepared lithium metal battery was charged and discharged between 2.2 and 3.9 V (1C current density of 150 mA g -1 ).
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a hierarchical pore positive electrode, characterized in that: The following steps are involved: (1) mixing a positive electrode active material I, a conductive agent I, an adhesive I and a solvent I into a first slurry, and coating the first slurry on a current collector, and removing the solvent I to form a first porous active material layer; (2) mixing the positive electrode active material II, the conductive agent II, the adhesive II, the pore former and the solvent II into a second slurry, and coating the second slurry on the first porous active material layer, and removing the solvent II to form a second porous active material layer; (3) heat-treating the current collector obtained in step (2) to remove the pore-forming agent in the second porous active material layer, thereby obtaining a graded pore positive electrode.
2. The method for preparing a hierarchical pore positive electrode according to claim 1, characterized in that: The positive electrode active material I and the positive electrode active material II are independently selected from LiFePO4, LiMn2O4 and LiNi x Co y Mn 1-x-y Any one of O2(0≤x≤1, 0≤y≤1).
3. The method for preparing a hierarchical pore positive electrode according to claim 1, characterized in that: The conductive agent I and the conductive agent II are independently selected from any one of carbon black, carbon nanotubes, carbon fibers and Ketjen black.
4. The method for preparing a hierarchical pore positive electrode according to claim 1, characterized in that: The adhesive I and the adhesive II are independently selected from any one of polyvinylidene fluoride, polytetrafluoroethylene and polyimide.
5. The method for preparing a hierarchical pore positive electrode according to claim 1, characterized in that: The solvent I and the solvent II are independently selected from any one of water, ethanol, N-methylpyrrolidone, N,N-dimethylacetamide, dimethylformamide and toluene.
6. The method for preparing a hierarchical pore positive electrode according to claim 1, characterized in that: The pore-forming agent is nitrite; the nitrite is magnesium nitrite.
7. The method for preparing a hierarchical pore positive electrode according to claim 1, characterized in that: In the step (1), the mass ratio of the positive electrode active material I, the conductive agent I and the adhesive I is (6-9.8): (0.1-2): (0.1-2).
8. The method for preparing a hierarchical pore positive electrode according to claim 1, characterized in that: In the step (2), the mass ratio of the positive electrode active material II, the conductive agent II, the adhesive II and the pore-forming agent is (4-9): 0.1-2: 0.1-2: (0.5-6).
9. The method for preparing a hierarchical pore positive electrode according to claim 1, characterized in that: The heat treatment temperature is 100-200° C. and the time is 6-24 hours.
10. The hierarchical pore positive electrode prepared by the method according to any one of claims 1 to 9, characterized in that: The invention comprises a current collector, on which a first porous active material layer and a second porous active material layer are arranged in sequence; the thickness of the first porous active material layer is 20-200 μm, and the thickness of the second porous active material layer is 50-320 μm.
Citation Information
Patent Citations
Thick electrode with good electrochemical performance and its preparation method
CN102324493A
Electrode with flame retardant additives and method and systems for preparation and use
CN112913056A
High-performance lithium ion battery thick pole piece and preparation method thereof
CN114400301A
Thick electrode plate, preparation method thereof and battery
CN115275094A